Asymmetric Confidentiality in Blockchain Embedded Smart Grids in Galois Field - Banerjee, Bannishikha; Jani, Ashish; Shah, Niraj (Frontiers in Blockchain, 2021)
Economic growth requires sharp increase in the utilization of energy. Financial development since the initial mechanical upheavals has been driven by industrialization, transportation, and most important of all electrification controlled by petroleum product ignition. This way of development has had malicious and abusive reverberations on the environment since the beginning. Smart grids are an idea to slightly diminish the burden on our mother nature. But this idea is getting tainted by the ferocious technophiles who are constantly trying to get the grid down using quantum computers. Thus, security becomes one of the major concerns for the smart grid. In this paper, we propose a quantum-resistant framework allying smart grids and blockchain embedded with a permutation-substitution-based public-key cryptosystem in Galois Field to prevent unauthorized access and perform encryption of user’s private information and consumption statistics. Permutation and substitution are performed to increase the diffusion and confusion of the data. Expenditures are quantified from the dissipation particulars and the remittance is performed using our blockchain wallet. The prediction model of consumption data is generated availing stochastic gradient descent. Performance analysis of the proposed cryptosystem is predicted after simulation of the smart grid.